The Effect of Milimani Law Courts Organizational Culture on Knowledge Management and Governance for Effective Administration of Justice - Luvuga, Joyce; Samita, Zacharia; Nalugala, Reginald (International Journal of Professional Practice, 2024)
Most organizations today regard knowledge as a strategic resource. However, the institutional culture in most organizations does not support the process of knowledge creation, storage, sharing and usage. This study sought to investigate the effect of Milimani Law Courts (MLC) organizational culture on Knowledge Management (KM) and governance for effective administration of justice in MLC in Nairobi, Kenya. The study targeted 180 staff members of Milimani Law Courts. Purposive sampling technique was used to select a sample of 124 respondents. The study adopted a mixed method approach. Interview schedule and semi-structured questionnaire were used to collect primary data. Quantitative data was analyzed using Statistical Package for Social Sciences (SPSS), while qualitative data was analyzed using Thematic Content Analysis (TCA), and findings presented in Tables and figures. Results revealed that the Judiciary has attempted adoption of an Information and Communication Technology (ICT) culture to improve KM and governance for effective administration of justice, through the adoption of case management systems. However, judgments are not stored in the case management systems. Additionally, findings indicated that the current staff motivation culture does not reward employees for sharing knowledge with colleagues, and that KM and governance aspects are not recognized. Consequently, knowledge creation, archiving and sharing is neglected. The study also found that the structure of various departments is not open for sharing knowledge, limiting employees’ interaction with one another. The study recommends the judiciary to adopt a culture that encourages creation and sharing of knowledge through staff rewards, use of ICT, democratic leadership style, and open spaces.